Prednosti in nevarnosti teledela - perspektive uvajanja teledela v Sloveniji - Trček, Franc (Uporabna informatika (Ljubljana), 2000)
With thw widwspread of informatisation teleworking gains new forms and contents, thus enabling the increase of temporary and permanent teleworkers. In the article, the author presents and defines some critical benefits of teleworking for emplozees and employers, and impacts of the increasing number of teleworkers upon regional development. Following the findings of foreign and own research and the results of the research Internet Use in Slovenia, there is an analysis of the current status of teleworking in Slovenia. In the conclusion the author presents some necessary elements of national policy of informatisation, needed for the future development of teleworking in Slovenia.
Keywords: delo na daljavo; prednosti; slabosti; Slovenija; teledelo